Engaging Leaders Promote Employees’ Well-Being at Work (Proceedings of the International Conference on Public Health, 2020)
This is a longitudinal study with one-year panel design and included 412 Indonesian employees from a state-owned company. The data was collected by a survey at time 1 (April-June 2017) and time 2 (April-July 2018) from participants who returned the questionnaire at both times. Structural Equation Modeling by Amos was performed to test the hypotheses. The result supported the hypotheses that engaging leadership at time 1 directly and positively predicted work engagement at time 2, and indirectly via the fulfilling basic need satisfaction at time 1 (partial mediation). The model showed an acceptable fit with the data (χ2= 48.70, df= 32, p< 0.03; RMSEA= 0.03; SRMR= 0.01; CFI=0.99; TLI=0.98). The result suggests that employees’ work-related basic needs are important to be fulfilled in order to increase their well-being namely, their work engagement, and engaging leaders have important part to satisfy those basic needs. Hence, it is suggested for companies or organizations to foster engaging leaders through leadership development programs.
Keywords: engaging leadership, basic need satisfaction, work engagement, longitudinal study.